The study of pitting corrosion on mild steel and stainless steel sample using electrochemical noise technique - Izyan Hazwani Hashim, 1986- 174889; Khaidzir Hamzah,lcsupervisor; Fakulti Sains 8004 (2008)
Project Paper (Sarjana Muda Sains (Fizik)) - Universiti Teknologi Malaysia, 2008